The Wilderness of Dragons. The reception of dragons in thirteenth century Iceland - Cutrer, Robert E., 1984- (2012)
Analysis of the mythic, literary, historical, and archaeological influences of dragons in Thirteenth century. This is followed by in-depth analysis of functions of dragons within thirteenth century texts. Thorough analysis of uses within fornaldarsögur and riddarasögur yields patterns that may be applied to other genres, such as Saint's lives and Histories.